2021
DOI: 10.3928/02793695-20201210-04
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Loneliness and Social Isolation With Self-Care Ability Among Older Adults

Abstract: The current study aimed to assess the relationship of loneliness and social isolation with self-care ability (SCA) among older adults. Participants were 170 older adults randomly recruited from seven urban health care centers in Gonbad Kavus, Iran. Data were collected using a personal characteristics questionnaire, the UCLA Loneliness Scale, Lubben Social Network Scale, and Self-Care Ability Questionnaire for the Elderly. Findings showed that 72.9% of participants reported mild loneliness and 2.4% reported sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In other words, individuals with a high level of self-care are less likely to experience the feeling of loneliness, which in turn, may cause them to experience lower level of depression in them. Although no study has investigated this path, the finding of this study are consistent with that of previous studies [ 27 , 46 ] in terms of the consistent relationships of this pathway. Regarding the interpretation of this finding, Canjuga et al [ 82 ] believe that the elderly who have adequate knowledge and ability in self-care and an effective support system, are capable enough to increase their emotional, religious, and physical health, and to independently maintain their social participation, which in turn, lead them to experience a lower feeling of loneliness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, individuals with a high level of self-care are less likely to experience the feeling of loneliness, which in turn, may cause them to experience lower level of depression in them. Although no study has investigated this path, the finding of this study are consistent with that of previous studies [ 27 , 46 ] in terms of the consistent relationships of this pathway. Regarding the interpretation of this finding, Canjuga et al [ 82 ] believe that the elderly who have adequate knowledge and ability in self-care and an effective support system, are capable enough to increase their emotional, religious, and physical health, and to independently maintain their social participation, which in turn, lead them to experience a lower feeling of loneliness.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed loneliness is an essential index of mental health and quality of life in the elderly that widely increases the probability of physical and mental diseases during old ages [ 41 ]. Accordingly, on the one hand, the results of studies have indicated that loneliness is significantly correlated with meaning of life [ 42 , 43 ], psychological well-being [ 44 , 45 ], self-care [ 46 ], and social capital [ 47 , 48 ]. On the other hand, loneliness seems to be a significant predictor of depression [ [49] , [50] , [51] ] and death anxiety [ [52] , [53] , [54] ].…”
Section: Introductionmentioning
confidence: 99%
“…Both fatty fish and vegetable oils are strongly associated with improved health in multiple domains [ 31 , 32 ], while the data on dairy is more mixed though in favor of consumption [ 33 , 34 ]. The strongest association was seen for social interaction, which is likely due to people lacking social support networks having fewer resources to play on in the face of health problems, and that lonely people are more likely to demonstrate less health-promoting behaviors [ 35 , 36 ]. Looking at multiple behaviors and multiple domains of intrinsic capacity together is important as individuals partake in multiple behaviors and can have multiple functional impairments.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been observed that widowed persons who do not have support from a loved one find it more difficult to cope with different aspects of life, including in particular the physical 27 and social 28 ones, as compared with people who are married or who are single by choice. Authors of studies on patients with chronic conditions indicate that loneliness has a significant negative impact on self-care ability, 29 adherence 30 and quality of life. 31 Similarly to studies on patients with cardiac problems, 32 our study found moderate levels of loneliness in the patients surveyed, which had a significant negative impact on the perceived quality of life and negatively influenced satisfaction with the medical services received.…”
Section: Discussionmentioning
confidence: 99%